Microtubule destabilization caused by particulate matter contributes to lung endothelial barrier dysfunction and inflammation - Karki, Pratap (Cell Signal, 2018)
Exposure to particulate matter (PM) associated with air pollution remains a major public health concern, as it has been linked to significant increase in cardiopulmonary morbidity and mortality. Lung endothelial cell (EC) dysfunction is one of the hallmarks of cardiovascular events of lung exposure to PM. However, the role of PM in acute lung injury (ALI) exacerbation and delayed recovery remains incompletely understood. This study tested a hypothesis that PM augments lung injury and EC barrier dysfunction via microtubule-dependent mechanisms. Our data demonstrate that in pulmonary EC PM caused time- and dose-dependent remodeling of actin cytoskeleton and considerable destabilization of the microtubule (MT) network. These events led to the weakening of cell junctions and formation of actin stress fibers, resulting in disruption of lung EC monolayer and increased permeability. PM also caused ROS-dependent activation of MT-specific deacetylase, HDAC6. Suppression of HDAC6 activity by pharmacological inhibitors or siRNA-based depletion of HDAC6 abolished PM-induced EC permeability increase, which was accompanied by reduced activation of stress kinase signaling, inhibition of Rho cascade, decreased IL-6 production and suppressed activation of its downstream target STAT3. Pretreatment of pulmonary EC with IL-6 inhibitor led to inhibition of STAT3 activity and decreased PM-induced hyper-permeability. Because one of the major activators of Rho-GTPase, GEF-H1, is localized on the MT, we examined its involvement in PM-caused EC barrier compromise. Inhibition of GEF-H1 activation significantly attenuated PM-induced permeability increase. Moreover, combined inhibition of IL-6 and GEF-H1 signaling exhibited additive protective effect. Taken together, these results demonstrate a critical involvement of MT-associated signaling in the PM-induced exacerbation of lung EC barrier compromise and inflammatory response.